2021
DOI: 10.3390/buildings11070286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fiber Shape and Volume Content on the Performance of Reactive Powder Concrete (RPC)

Abstract: This research studied the influence of three types of open (short-straight, long-straight, semicircular) and three different shapes of closed steel fibers (triangular, rectangular, circular) with different fiber contents by volume (0, 0.5%, 1%, 1.5%, and 2%) on the working and mechanical performance of reactive powder concrete (RPC). The results indicated that (1) the number of steel fibers and the enclosed area formed by closed steel fibers would remarkably impact the performance of RPC; (2) the semicircular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…It showed that appropriate ratio of length to diameter will give full play to the tensile effect of steel fiber in the material and ensure it is evenly distributed. Chuanlin Wang [12] studied the influence of three types of open and three different shapes of closed steel fibers on the working and mechanical performance of RPC, showing that the open steel fibers enhance the mechanical performance of RPC via their anchoring performance while the closed steel fibers work by confining the concrete. Qin Rong [13] studied the dynamic response of RPC columns based on the equivalent single-degree-offreedom method and P-I curve and obtained the effect of five parameters on the degree of damage under different blast loadings, which provides a valuable reference for the dynamic response of RPC members.…”
Section: Introductionmentioning
confidence: 99%
“…It showed that appropriate ratio of length to diameter will give full play to the tensile effect of steel fiber in the material and ensure it is evenly distributed. Chuanlin Wang [12] studied the influence of three types of open and three different shapes of closed steel fibers on the working and mechanical performance of RPC, showing that the open steel fibers enhance the mechanical performance of RPC via their anchoring performance while the closed steel fibers work by confining the concrete. Qin Rong [13] studied the dynamic response of RPC columns based on the equivalent single-degree-offreedom method and P-I curve and obtained the effect of five parameters on the degree of damage under different blast loadings, which provides a valuable reference for the dynamic response of RPC members.…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to solve this problem is by adding dispersed fiber reinforcement to the cement matrix, which can significantly increase its tensile and flexural strength, crack resistance, resistance to impact and vibration, etc. [5][6][7][8]. Fiber-reinforced concrete has increased abrasion resistance as well as resistance to cracking [9].…”
Section: Introductionmentioning
confidence: 99%
“…Such fibers enhance the new contact between the fibers and mortar and stop fractures from forming. 19 It not only boosts the concrete tensile capacity but also significantly affects the material's conductivity, stability, and durability. 20 The kind of fiber and fiber-concrete mix interface qualities influence the characteristics of the concrete.…”
Section: Introductionmentioning
confidence: 99%